Age and maturity related differences in motor coordination among male elite youth soccer players? - Rommers, N.; Mostaert, M.; Goossens, L.; Vaeyens, R.; Witvrouw, E.; Lenoir, M.; D`Hondt, E. (Journal of Sports Sciences, 2019)
This study investigated differences in generic and soccer specific motor coordination, as well as speed and agility depending on age and maturity in elite youth soccer players (U10-U15, N = 619). Measurements included body height, body weight and sitting height to estimate age at peak height velocity (APHV); three Körperkoordinationstest für Kinder subtests (i.e. jumping sideways (JS), moving sideways (MS), balancing backwards (BB)) to assess generic motor coordination; the UGent dribbling test for soccer specific motor coordination; a 5m/30m sprint and T-test for speed and agility, respectively. Age specific z-scores of the predicted APHV identified players as earlier, on time or later maturing. (M)ANOVA analyses showed significant age by maturity interaction effects for the speed and agility test cluster, revealing maturity related differences in U14 and U15 players. Next to an overall higher performance with age for all test clusters (?2 0.080-0.468), earlier maturing players outperformed their later maturing peers in 5m/30m sprinting. The opposite was seen for JS and BB. So, players` maturity status should be taken into account to adequately value performance in talent identification. Also, the focus on characteristics that appear to be minimally biased by an earlier maturational timing (i.e. motor coordination) should be increased.